Etika Transformatif Pendidik: Studi Hermeneutis Al-Qur'an dan Hadis dalam Adabul ‘Alim An-Nawawi - Ali Masdar Fahim (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2026)
Studies on teacher ethics based on the Qur'an and Hadith tend to be thematic-descriptive without analyzing classical scholars' istinbath methods. This research hermeneutically analyzes teacher ethics through Adabul ‘Alim by Imam An-Nawawi to identify referenced texts, analyze istinbath methods, reconstruct ethical structures, and assess relevance for contemporary Islamic education. Qualitative library research with hermeneutical approach was employed through textual analysis, argumentative structure analysis, hermeneutical analysis, and conceptual synthesis of Adabul ‘Alim. Findings show An-Nawawi referenced four Qur'anic verses and five hadiths with layered istinbath patterns (norm-warning-praxis) characteristic of Shafi'i methodology. This study reconstructs four hierarchical transformative ethical dimensions: spiritual-intentional (foundation), epistemic-academic (scholarly integrity), relational-pedagogical (humanization), and transformative-social (agent of change). This framework is relevant for strengthening teacher professionalism, academic integrity, and educators' transformative roles in contemporary Islamic education.